Comparing randomized controlled trials of outpatient family‐based or inpatient multimodal treatment followed by outpatient care in youth with anorexia nervosa: Differences in populations, metrics, and outcomes. (26th April 2022) - Haas, Verena; Nadler, Janine; Crosby, Ross D.; Madden, Sloane; Kohn, Michael; Le Grange, Daniel; Gonçalves, Ana Sofia Oliveira; Hebebrand, Johannes; Correll, Christoph U.
Abstract: Objective: Various approaches exist to treat youth with anorexia nervosa (AN). Family‐based treatment (FBT) has never been compared to long inpatient, multimodal treatment (IMT) in a randomized controlled trial (RCT). The aim of this study was to compare data on body weight trajectories, change in eating disorder psychopathology, hospital days and treatment costs in RCTs delivering FBT or IMT. Method: Review of RCTs published between 2010 and 2020 in youth with AN, delivering FBT or IMT. Results: Four RCTs delivering FBT (United States, n  = 2; Australia, n  = 2), one RCT delivering Family Therapy for AN (United Kingdom) and two RCTs delivering IMT (France, n  = 1; Germany, n  = 1) were identified from previous meta‐analyses. The comparison of studies was limited by (1) significant differences in patient baseline characteristics including pretreated versus non‐pretreated patients, (2) use of different psychometric and weight measures and (3) different initial velocity of weight recovery. Minimal baseline and outcome reporting standards for body weight metrics and nature/dose of interventions allowing international comparison are needed and suggestions to developing these standards are presented. Discussion: An RCT should investigate, whether FBT is a viable alternative to IMT, leading to comparable weight and psychopathology improvement with less inpatient time and costs. Highlights: So far, family‐based treatment (FBT) has not been compared with inpatient, multimodal treatment (IMT) in a randomized controlled trial (RCT). Comparison of aggregated outcome data from published RCTs delivering either FBT or IMT was of limited scientific validity due to differences in patient characteristics and methodology, in particular, the use of different weight metrics. International consensus for standardization of outcome measures in youth with anorexia nervosa (AN) is urgently needed. An RCT comparing FBT and IMT has the potential to broaden treatment options for youth with AN.